Persistent States: Lessons for Scottish Devolution and Independence - Anton Muscatelli; Graeme Roy; Alex Trew (Center for Economic Studies and ifo Institute (CESifo), 2022)
The equilibrium size of a nation state is, in part, the result of a trade-off between the gains from scale economies in the provision of public services and the costs of applying uniform policy to heterogeneous cultural, institutional, and geographical fundamentals. Changes in such fundamentals can thus place pressure on states to reform over time. We consider this dynamic state formation process in the context of Scotland within the UK. First, we review the recent research in economic history on the persistence and evolution of such fundamentals. Second, we consider the history of Scotland both before and after the 1707 Act of Union in the light of that broader economic history literature. We conclude with some implications of fundamental persistence for current debates on the place of Scotland within the UK.
Keywords: H77; N43; N44; 330; Scotland; persistence; state formation